HISTORICAL ASSESSMENT OF ATMOSPHERIC PERSISTENT ORGANIC POLUTANTS DEPOSITIONS IN MUNTINU GLACIAL LAKE, SOUTHERN ROMANIAN CARPATHIANS, BASED ON RADIONUCLIDE-DATED SEDIMENTS - PĂNESCU, Vlad Alexandru; BEGY, Robert; ROȘIAN, Gheorghe; BRUZZONITI, Maria Concetta; BELDEAN-GALEA, Mihail Simion (Studia Universitatis Babeș-Bolyai Chemia, 2022)
This study aims to assess the pollution history of persistent organic pollutants (POP) in lake Muntinu, Carpathian Mountains, Romania. Gamma spectrometry was used to measure 210Pb and 137Cs radionuclides in order to determine the age of sediment layers. The target compounds were isolated from sediment samples by ultrasound-assisted extraction method, followed by purification of extracts using open-column chromatography. 16 polycyclic aromatic hydrocarbons (PAHs), 20 organochlorine pesticides (OCPs) and 12 polychlorinated biphenyls (PCBs) were analysed in each dated sediment layer using gas chromatography coupled with mass spectrometry or electron capture detector. The results show that, over the past 100 years, POP concentrations from sediment samples ranged from 2.53 to 156.27 ng/g for PAHs, from 1.78 to 71.12 ng/g for OCPs, and from not detected to 76.03 ng/g for PCBs. PAHs diagnostic ratios such as ƩLMW/ƩHMW, ANT/(ANT+PHE) and FLT/(FLT+PYR) show that the main source of PAHs in the sediment is of pyrogenic nature, especially from biomass and coal combustion. The sources of OCPs and PCBs could not be determined due to the lack of data obtained. However, the study demonstrates that the analysis of POP residues in sediments is a suitable method for reconstructing the history of surface water pollution.